The ordination of women in the Catholic Church? New considerations. Issue 2 (2nd July 2016) - Grey, Mary
Abstract : This article responds to the two articles by Sister Catherine Droste and Roy Bourgeois (ISCE Vol 7. No.1 2015) by putting the issue of the Ordination of Women into a wider ecclesial context. Building on Pope Francis's bringing Liberation Theology into central focus, seeking justice for the poorest and vulnerable people, the article argues that justice for women is an urgent issue. Focusing not directly on Ordination to the Priesthood in the Catholic Church, the article argues for the restoration of the diaconate for women, on historical, theological and ecclesial grounds. The most forceful argument is that women are already carrying out the ministry of the diaconate in many ways, so Ordination would recognise this truth and confirm women in this role for the upbuilding of community in the Church.